An easily sintered, chemically stable, barium zirconate-based proton conductor for high-performance proton-conducting solid oxide fuel cells - Shi, Zhen (2014)
Yttrium and indium co-doped barium zirconate is investigated to develop a chemically stable and sintering active proton conductor for solid oxide fuel cells (SOFCs). BaZr0.8Y0.2-xInxO3- δ possesses a pure cubic perovskite structure. The sintering activity of BaZr0.8Y0.2-xInxO3- δ increases significantly with In concentration. BaZr0.8Y0.15In0.05O3- δ (BZYI5) exhibits the highest total electrical conductivity among the sintered oxides. BZYI5 also retains high chemical stability against CO2, vapor, and reduction of H2. The good sintering activity, high conductivity, and chemical stability of BZYI5 facilitate the fabrication of durable SOFCs based on a highly conductive BZYI5 electrolyte film by cost-effective ceramic processes. Fully dense BZYI5 electrolyte film is successfully prepared on the anode substrate by a facile drop-coating technique followed by co-firing at 1400 °C for 5 h in air. The BZYI5 film exhibits one of the highest conductivity among the BaZrO3-based electrolyte films with various sintering aids. BZYI5-based single cells output very encouraging and by far the highest peak power density for BaZrO3-based proton-conducting SOFCs, reaching as high as 379 mW cm−2 at 700 °C. The results demonstrate that Y and In co-doping is an effective strategy for exploring sintering active and chemically stable BaZrO3-based proton conductors for high performance proton-conducting SOFCs.